Amplifying Meteorological Droughts Across Middle- and Low-Latitude Northern Hemisphere - Wang, Danzhou; Zhang, Qiang; Singh, Vijay P.; Shen, Zexi; Wang, Gang; Wu, Wenhuan; Yuan, Ruyue (Frontiers in Earth Science, 2022)
Drought changes and the underlying causes have, in the backdrop of warming climate, aroused widespread concern. However, exact changes in patterns of meteorological droughts in both space and time are still open for debate. The Northern Hemisphere is home to 90% of the world’s population and has been afflicted by droughts over time. Here we present the evolution of spatiotemporal patterns of meteorological droughts, quantified by standardized precipitation evapotranspiration index across the Northern Hemisphere and related causes during a period of 1961–2018. We found amplifying droughts characterized by higher frequency, longer duration, and stronger severity across middle- and low-latitudes of the Northern Hemisphere, specifically, Mongolia, China and Central Asia expanding along central Eurasia, Circum-Mediterranean region, and southwestern North America (NA). Russia, Central Asia, China and the Indian Peninsula are regions with frequent droughts. Period of 1961–2018 witnessed spatial evolution of droughts in counterclockwise direction over North America. In general, the spatial evolution of meteorological droughts in Northern Hemisphere also followed counterclockwise direction due to the atmospheric pressure belt, wind belt, atmospheric circulation, and sea-land breeze. SPEI-based droughts were in close relation with El Niño-Southern Oscillation (ENSO) and Atlantic Multidecadal Oscillation (AMO). In particular, La Niña phenomenon could dry out southern NA and central and western Russia; and Atlantic Multidecadal Oscillation might affect the spatiotemporal variation of the drought in mid-high latitudes. These findings help understand meteorological droughts in the context of global warming.